Associations entre la diversité génétique et la performance individuelle chez le caribou migrateur (Rangifer tarandus) du nord du Québec et du Labrador - Gagnon, Marianne (Université Laval, 2018)
Associations between genetic diversity and individual performance may indicate inbreeding depression or selective pressures applied on some functional loci in a population. In this study, we looked at the association of genetic diversity with performance traits (annual survival and body mass) in migratory caribou of two declining herds in Québec and Labrador. We assessed genetic diversity at two genetic scales: i) genome-wide diversity estimated with 22,073 single nucleotide polymorphisms and ii) diversity of one locus (DRB) of the major histocompatibility complex (MHC). During the 20-year sampling period, genome-wide and MHC-DRB diversity remained stable. Genome-wide diversity was not associated with performance, but MHC-DRB functional diversity showed a negative association with annual survival of adults. Furthermore, we found a slight differentiation of the two herds that were considered until now as a single population from a genetic point of view. Our results suggest that the rapid decline of both herds did not lead to a loss of genetic diversity, even though an increase in genetic drift could be responsible for the genetic structure we observed. They also suggest that the herds do not suffer from inbreeding depression despite their marked decline. The negative association of MHC-DRB diversity with survival is opposite to the majority of studies published on this matter that usually show a positive association. Our results suggest that MHC diversity might not be beneficial in ecosystems with low pathogen diversity or in which pathogen abundance changes quickly in response to climate change. Les liens entre la diversité génétique et la performance individuelle peuvent révéler l’existence de dépression de consanguinité ou de sélection naturelle à certains loci fonctionnels dans une population. Dans cette étude, nous avons étudié l’association de la diversité génétique avec des traits de performance (survie annuelle et masse corporelle) chez le caribou migrateur appartenant à deux populations en déclin au ...